2015
DOI: 10.1002/pbc.25592
|View full text |Cite
|
Sign up to set email alerts
|

Renal medullary carcinoma and sickle cell trait: A systematic review

Abstract: Sickle cell trait (SCT) carries a small risk of renal medullary carcinoma (RMC). We conducted a systematic literature review and reported new four RMC cases (total N = 217). Eighty eight percent had SCT and 8% had sickle cell disease; 50% were children. Males had 2.4× risk than females. Isolated hematuria or in combination with abdominal or flank pain was the presenting sign in 66% cases. Tumor-related mortality was 95%. Four non-metastatic patients were long-term disease-free survivors. Although risk appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 80 publications
(198 reference statements)
5
110
0
2
Order By: Relevance
“…The most common metastatic sites include lymph nodes, lungs, liver, adrenal glands, and bone. [1] Some patients first present with signs of metastatic disease as was seen in our patient who presented with cough and shortness of breath.…”
Section: Brief Review Of the Topicmentioning
confidence: 76%
See 1 more Smart Citation
“…The most common metastatic sites include lymph nodes, lungs, liver, adrenal glands, and bone. [1] Some patients first present with signs of metastatic disease as was seen in our patient who presented with cough and shortness of breath.…”
Section: Brief Review Of the Topicmentioning
confidence: 76%
“…Eighty-eight percent of the patients have sickle cell trait. [1] It has a poor prognosis with an overall survival of 4 months in patients with metastases and 17 months without. [2] Widely metastatic disease at the time of diagnosis is typical.…”
Section: Brief Discussion With Follow-upmentioning
confidence: 99%
“…The mean duration of life after surgery was 15 weeks. In 2015, Alvarez et al [3] published the first systematic review of the 217 RMC cases reported to date, 88·6% of which were associated with SCT. Median overall survival was 10 months.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been published describing the role of surgery, chemotherapy, immunotherapy, stem cell transplant, or radiation in the treatment of RMC but have found unfavorable outcomes with an overall mortality of 95% [3,4]. The two most commonly used chemotherapy regimens have been the high-dose intensity methotrexate, vinblastine, doxorubicin, and cisplatin (MVAC) and paclitaxel, cisplatin or carboplatin, and gemcitabine (PCG).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation